Does exporting increase productivity of Thai firms via linkage spillovers? - Kornkarun Cheewatrakoolpong; Tanapong Potipiti (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2014)
Several studies using firm-level data could not find significant evidence to support that exporting activities promote productivity growth. However, few studies have considered whether exporting companies can create spillovers to domestic firms. In fact, exporting companies create positive productivity spillovers to their domestic peers (horizontal spillovers), suppliers (backward linkage spillovers) and buyers (forward linkage spillovers). This paper investigates the existence of productivity spillovers via backward, forward and horizontal linkages from exporting firms to other firms, based on Thai firm-level data. In contrast to existing literature on firms' productivity, which uses a firm-level dataset to conclude that exporting activities make no contribution to productivity growth of firms, the authors find that backward linkages are the most important spillover channel for exporting firms. Also, the current study finds that export destinations are an important factor in supporting linkage spillovers; only exporting to developed countries creates backward linkage spillovers. Moreover, exporting firms gain most spillovers from backward linkages. Finally, the authors show that productivity spillovers from domestic suppliers are more important than outsourcing.
Keywords: F14; F61; 330; Exports; Forward linkages; Backward linkages; Productivity; Spillovers